Fingerprint of anthropogenic climate change detected in long-term western North American fire weather trends - Laura E. Queen; Sam Dean; Dáithí Stone; Piyush Jain; James Renwick; Nathanael Melia; Yukiko Imada (Communications Earth & Environment)
Abstract The anthropogenic fingerprint has been detectable in observed global climate change for decades, yet it is still difficult to detect at the regional scale beyond temperature due to the presence of large internal variability and modeling and observational uncertainties. Here we demonstrate regional optimal fingerprinting of long-term fire weather trends in western North America, leveraging large ensembles of high resolution, atmosphere-only climate models to adequately sample internal variability. Considering the full spatiotemporal response to thermodynamic and dynamic climate change, we find that anthropogenic forcings have contributed 81–188% of the region’s observed increasing linear trend in fire weather over the last 50+ years. The natural fingerprint, which contains inter-annual and decadal variability, is also robustly detected. We detect the anthropogenic fingerprint in relevant meteorological variables – temperature, precipitation, and relative humidity – and link model differences in fire weather response to differences in simulated precipitation and relative humidity responses.